Pérdida de un familiar y su incidencia en la salud mental de una mujer de 20 años de edad en la ciudad de Babahoyo - Viera Erazo, Veronica Belen (2022)
Losing a family member is more common today as the COVID-19 pandemic has yet to fully dissipate. Therefore, this case study focuses on the incidence of the loss of a family member on the mental health of a 20-year-old person, who was allowed to reach a diagnosis with the help of different techniques such as clinical observation, semi-structured interview and With tools such as clinical history, observation guide and psychometric batteries, in conclusion it was possible to analyze the way in which the loss of a relative affects the patient, giving a diagnosis based on the ICD-10 (2000) F32 criteria. 1 Depressive disorder in a moderate episode and a therapeutic plan based on the cognitive behavioral approach is recommended in which different techniques of this approach were used to reduce the symptoms and modify the different distorted thoughts that the young woman presented.